ANALISIS KINERJA PEGAWAI NEGERI SIPIL DI BAGIAN PERENCAAN DAN KEUANGAN SEKRETARIAT DAERAH KANTOR BUPATI KABUPATEN MALANG: Performance Analysis Of Civil Servants In Planning And Finance Regional Secretariat Of The Regent's Office Malang Regency - Fitria Erika Sari; Yeny Eva Damayanti (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
This service is carried out to find out what the performance of civil servants is like, so that you can also find out about the State Civil Apparatus (ASN), and the types of civil servants (PNS) and also PPPK. In this service using qualitative methods, the object of this research uses secondary data data originating from literature such as journals, articles, and so on. Data collection techniques are observation and documentation. The types of data that we use in this service are primary data through observation techniques and secondary data in the form of documentation. The data analysis method used in this service is a qualitative descriptive analysis method, namely collecting data, compiling data, presenting data, interpreting data, and drawing conclusions from the data that has been collected. The results of this dedication show that a civil servant fulfills the job requirements set by an agency or body that carries out the duties and functions of the government.